2006
DOI: 10.1038/ncprheum0245
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral therapy for fibromyalgia

Abstract: Cognitive behavioral therapy (CBT) techniques offer short-term, goal-oriented psychotherapy. In this respect, it differs from classical psychoanalysis in emphasizing changes in thought patterns and behaviors rather than providing 'deep insight'. Importantly, the beneficial effects of CBT can be achieved in 10-20 sessions, compared with the many years required for classical psychoanalysis. Although CBT is often done on a one-to-one basis, it also lends itself to a group therapeutic setting. CBT was initially us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 43 publications
1
84
0
8
Order By: Relevance
“…One study found that patients receiving educational intervention had significantly more improvement than controls and that the beneficial effects continued for 3 to 12 months after the sessions had ended (Goldenberg et al, 2004). A meta-analysis of randomized clinical trials using cognitive behavioral therapy showed it could reduce fear of pain and fear of activity (Bernardy et al, 2010); however, it provided little benefit as single modality except possibly in juvenile FMS (Bennett and Nelson, 2006). Comprehensive reviews of Chinese stress reduction exercise programs, such as tai-chi and qigong, reported improvement of symptoms in FMS patients but with little difference when compared with controls (Mist et al, 2013;Sawynok and Lynch, 2014).…”
Section: Treatmentmentioning
confidence: 99%
“…One study found that patients receiving educational intervention had significantly more improvement than controls and that the beneficial effects continued for 3 to 12 months after the sessions had ended (Goldenberg et al, 2004). A meta-analysis of randomized clinical trials using cognitive behavioral therapy showed it could reduce fear of pain and fear of activity (Bernardy et al, 2010); however, it provided little benefit as single modality except possibly in juvenile FMS (Bennett and Nelson, 2006). Comprehensive reviews of Chinese stress reduction exercise programs, such as tai-chi and qigong, reported improvement of symptoms in FMS patients but with little difference when compared with controls (Mist et al, 2013;Sawynok and Lynch, 2014).…”
Section: Treatmentmentioning
confidence: 99%
“…A metaanalysis of 13 studies of cognitive-behavioural therapy for fibromyalgia showed that in most studies there were worthwhile improvements in pain-related behaviour, selfefficacy and overall physical function, with particular Fibromyalgia: psychiatrists should now be picking up the baton Leigh A. Neal 1 benefits for juveniles. 10 A meta-analysis of 26 randomised controlled studies of antidepressants in fibromyalgia concluded that amitriptyline, selective serotonin reuptake inhibitors and serotonin and noradrenaline reuptake inhibitors are probably all effective in the treatment of fibromyalgia. 11 In addition, individuals with fibromyalgia report a considerable impact on their quality of life and their perceived disability level seems to be influenced by their mental health condition.…”
Section: Scientific Basis For Fibromyalgia As a Psychiatric Conditionmentioning
confidence: 99%
“…Başlangıcı 1950'lerde ilk Alber Ellis'in akılcı duygusal terapi terimini ortaya attığı dönemlere dayanmaktadır. Sonrasında Aeron Beck 1960'ların başlarında depresyon tedavisinde bilişsel terapiyi kullanmış, 1970'lerde ise Michael Mahoney ilk kez davranış modifikasyon prensiplerini uygulamıştır ve son olarak Donald Meichenbaum ise stresle başa çıkma ve stres yönetimi için yeni bir yaklaşım geliştirerek adını bilişsel davranışsal modifikasyon koymuştur (62). Akut ağrı sırasında koruyucu rol oynayan davranışsal (kaçınma davranışı), bilişsel (katastrofizm, bedensel duyumlara karşı dikkat artışı) ve fizyolojik (otonom cevabın ve kas gerginliğinin artması) reaksiyonlar ortaya çıkmakta ancak bu reaksiyonlar kronik ağrıda olduğu gibi uzun dönem devam ettiğinde zararlı ve etkisiz hale gelmektedir (59).…”
unclassified
“…Multidisipliner ve interdisipliner tedavilerin etkinliğini araştırmak için yapılan meta-analizler sonucunda, egzersiz ve eğitim programlarının bir arada uygulanması gerektiği vurgulanmaktadır (59). Yapılan çalışmalar, bu tedavi yaklaşımlarının protokollerinde uygulanan egzersiz programlarının etkinliklerini desteklemektedir ve BDT gibi psikolojik girişimlerle kombine edildiğinde etkinliğin daha da arttığını göstermektedir (3,17,62,70). Günümüze kadar yapılan çalışmalarda, multidisipliner ve interdisipliner tedavilerin etkinlikleri gösterilmiştir, ancak içeriklerinde uygulanan tedavi komponentlerinden hangisinin daha etkili olduğu konusu halen tartışmalıdır (66 …”
unclassified